Romans an exposition of chapter 7:1-8:4, the law: its functions and limits - Lloyd-Jones, David Martyn (London The Banner of Truth Trust, 1973)
"These sermons were preached on Friday nights in Westminster Chapel, London, during the period April 1959-February 1960." Includes the text of Romans vii, 1,-viii, 4.
Keywords: Bible. -- Romans VII, 1-VIII, 4 -- Criticism, interpretation, etc. Sermons, English. Bible.--N.T.--Romans.